Field-effect Based pH Sensors for Cutting Fluid Condition Monitoring. (2015) - Güth, Frederic; Arki, Pal; Joseph, Yvonne
Abstract: Field-effect basedE lectrolyteI nsulatorS emiconductor (EIS) structures were used to monitor the degradation of cutting fluids under laboratory conditions. An initial set of experiments was carried out to evaluate the sensors' performance in terms of their sensitivity to degradation-induced pH changes. The results presented here show that the employed sensors are capable of differentiating between pristine and degraded cutting fluids as well as intermediate mixtures. We therefore suggest field-effect based pH sensors as promising candidates to be part of sensor arrays capable of delivering real-time information about the overall state of cutting fluids, which would enable a more cost efficient and environmental friendly fluid management.